Implementation of nationalism value in Ubrug based learning - Dewantara, Billy Julian; Aman, Aman (Universitas Negeri Yogyakarta, 2023)
This research aims to describe the instillation of nationalism values in ubrug-based learning. The research approach used is descriptive qualitative research. The research results indicate that the ubrug method or role-playing in instilling nationalism can enhance the students' nationalist attitudes. Students not only portray characters in the story being presented but also can extract the values contained in the performing arts, especially those related to nationalism, which is the goal of the learning process using the ubrug method or role-playing. Furthermore, the use of the Sundanese and Javanese Serang local languages continues to endure with the preservation of local wisdom, including folk theater like ubrug. However, the use of the local language also faces obstacles in the staging of ubrug within the school environment because there are students who are not native to Banten. Hence, they need to learn and adapt to the local language used in the ubrug theater performance.